KEBERADAAN DAN PENERAPAN PERATURAN DAERAH SYARIâAH SEBAGAI PERUNDANG-UNDANGAN PADA TINGKAT DAERAH - Setiawan, Dian Bakti (Soumatera Law Review, 2018)
One of issue which often emerge in local goverment in indonesia isÂ Â Peraturan Daerah syariah, that is local regulation based on islamic law. Result of this research conclude that the Peraturan Daerah syariah is transformation of syaria as islamic law into local regulation asÂ Â positive law. in side ofÂ Â legislation, itÂ Â can be assesed by using the principles of formulation of legislation and principles of material contens of legislation. To asses from perspective of human rights can be used three categories,Â Â that is: arranging worship, having the character of privat law,Â Â and having the character of publik law.Based onÂ Â two assesment instrument, Regulation Arranging worship and having character of private law should be assigned by central government through The Ministery of Religion Affairs, but syaria doctrinÂ having character of publik law can be poured into local regulation as material resources of law.Â Â Academically, the existence of Peraturan Daerah syariâah is motivated by Islamic doctrin onÂ Â the state in interpretation of Ibnu KhaldunÂ Â and Ibnu Taymia.Â Â This doctrin is related to the teachingÂ Â of Imam Malik thatÂ Â enable to releaseÂ Â the regulation such asÂ Â Peraturan Daerah SyariAh, althoughÂ Â not in the Islamic state. Practically, the Peraturan Daerah syariah is driven by political appointment while political campaign for local election. So far Peraturan Daerah SyariâahÂ Â is moreÂ as moral appeal rather than legals norm.